2017
DOI: 10.4172/2169-0022.1000364
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide Thin Films with Very Large Charge Carrier Mobility Using Pulsed Laser Deposition

Abstract: Large area reduced graphene oxide (RGO) thin films have been grown using pulsed laser deposition (PLD) technique. A very large carrier mobility of 372 cm 2 V -1 s -1 has been observed in a PLD grown RGO thin film with a large sp 2 carbon fraction of 87% along with narrow Raman 2D peak profile. The fraction of sp 2 carbon and carbon/oxygen ratios are tuned through PLD growth parameters, and these are estimated from X-ray photoelectron spectroscopy (XPS) data. The electrical properties of the RGO thin films are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…The green emission band at ~560 nm corresponded to the presence of defects site of oxygen vacancy in CNNG3LDH 29,30 . The new peak in the PL spectra of CNNG7LDH sample at around 410 nm is due to the characteristic spectrum for exfoliated graphene sheet 56 . Due to higher wt% loading of rGO in CNNG7LDH than other samples of the series, the peak is more prominent in CNNG7LDH.The PL peak intensity of green emission band at 568 nm was more intense in heterostructure CNNGxLDH, implying that the energy level of the surface trap oxygen vacancies sites varied due to the transformation of pristine NiFe LDH to NiFe LDH nanosheets 55 .…”
Section: Resultsmentioning
confidence: 87%
“…The green emission band at ~560 nm corresponded to the presence of defects site of oxygen vacancy in CNNG3LDH 29,30 . The new peak in the PL spectra of CNNG7LDH sample at around 410 nm is due to the characteristic spectrum for exfoliated graphene sheet 56 . Due to higher wt% loading of rGO in CNNG7LDH than other samples of the series, the peak is more prominent in CNNG7LDH.The PL peak intensity of green emission band at 568 nm was more intense in heterostructure CNNGxLDH, implying that the energy level of the surface trap oxygen vacancies sites varied due to the transformation of pristine NiFe LDH to NiFe LDH nanosheets 55 .…”
Section: Resultsmentioning
confidence: 87%
“…The XRD showed that TiO 2 and CuO were crystalline whereas GO was amorphous. Many studies have also shown that GO is amorphous (Bhaumik et al, 2017;Kumar, 2015; ACCEPTED MANUSCRIPT Mkhoyan et al, 2009;Shi et al, 2012) and semi-amorphous in nature (Malik et al, 2010;Pei and Cheng, 2011). This amorphous nature of GO is due to the warp from sp 3 C-O (Mkhoyan et al, 2009;Viet et al, 2010).…”
Section: Characterization Of Nanoparticles and Npcmsmentioning
confidence: 99%
“…Other contributions need to be added to achieve a proper deconvolution. Two broad bands at 1160 cm -1 and 1490 cm -1 , named bands T and F respectively [54][55][56], can also appear in the presence of sp 3 carbon atoms, i.e. amorphous carbon, aliphatic fraction or defects in the graphenic network.…”
Section: Pyrolysis Yieldsmentioning
confidence: 99%